2016
DOI: 10.1002/2015ja022060
|View full text |Cite
|
Sign up to set email alerts
|

Empirical model of the Martian dayside ionosphere: Effects of crustal magnetic fields and solar ionizing flux at higher altitudes

Abstract: We use electron density profiles measured by the Mars Advanced Radar for Subsurface and Ionosphere Sounding instrument on board the Mars Express spacecraft to investigate the effects of possible controlling parameters unconsidered in the empirical model of Němec et al. (2011, hereafter N11). Specifically, we focus on the effects of crustal magnetic fields and F10.7 proxy of the solar ionizing flux at higher altitudes. It is shown that while peak electron densities are nearly unaffected by crustal magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
(85 reference statements)
3
34
0
Order By: Relevance
“…Němec et al () used 30,283 MARSIS radar sounding profiles and almost 200,000 local electron density measurements to develop an empirical model of electron densities above the peak altitude, which assumes a Chapman dependence at altitudes below about 200 km (photochemically controlled region) and smoothly transits to an exponential dependence at altitudes above about 325 km (diffusion‐controlled region). The model performance at altitudes higher than about 200 km was later improved by incorporating dependences on crustal magnetic field magnitude and solar ionizing flux (Němec, Morgan, Gurnett, & Andrews, ).…”
Section: Introductionmentioning
confidence: 99%
“…Němec et al () used 30,283 MARSIS radar sounding profiles and almost 200,000 local electron density measurements to develop an empirical model of electron densities above the peak altitude, which assumes a Chapman dependence at altitudes below about 200 km (photochemically controlled region) and smoothly transits to an exponential dependence at altitudes above about 325 km (diffusion‐controlled region). The model performance at altitudes higher than about 200 km was later improved by incorporating dependences on crustal magnetic field magnitude and solar ionizing flux (Němec, Morgan, Gurnett, & Andrews, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, crustal magnetic fields have an important role at high altitudes. As Nĕmec et al 2016 have recently demonstrated, electron densities at high altitudes (in the diffusive region) are significantly increased over crustal magnetic field areas, while peak electron densities are nearly unaffected. Moreover, there is clear evidence that solar flux at these high altitudes is still significant (Nĕmec et al, 2016), the evolution of which with the solar cycle constitutes a clear future line of work.…”
Section: Discussion: Earth Ionosphere Comparisonmentioning
confidence: 65%
“…Turning to the empirical representation of the topside ionosphere in the model by Němec et al () resulted in better agreement with MAVEN results (Mendillo, Narvaez, Vogt, Mayyasi, Mahaffy, et al, ). To achieve full altitude coverage in MIRI, we took the normalized shapes of the Němec et al () profiles above h max for all SZAs and merged them with the normalized shapes of the theoretical profile below h max for all SZAs. These are shown as Figure .…”
Section: The Miri Approachmentioning
confidence: 85%
“…Electron density profiles formed by merging the topside of normalized climatological profiles (Němec et al, ) and the bottomside of normalized theoretical profiles (Mayyasi & Mendillo, ) for each solar zenith angle bin. These are calibrated by the peak density MIRI‐2013 predicts.…”
Section: The Miri Approachmentioning
confidence: 99%
See 1 more Smart Citation